SISTEM INFORMASI REKAM MEDIS BERBASIS WEBSITE PADA KLINIK MULYAJATI PENDEGLANG BANTEN MENGGUNAKAN MODEL WATERFALL - Andriana, Dedi; Latifah, Fitri (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Although Mulyajati Clinic in Pandeglang has been serving the community for several years, Mulyajati Clinic still faces challenges in managing patient medical records. Currently, the medical record recording system used is still manual, with patient files stored in physical form in archive folders. This process causes a number of operational and administrative problems that impact the efficiency and quality of service. design of this application, the waterfall system development model (SDLC) is used. The waterfall model is often referred to as the linear sequential model or the classical life flow The results of the analysis and analysis of the Mulyajati Pandeglang Clinic Information System show that the system aims to help the medical staff who work there and facilitate patient data collectionThis medical record information system will make it easier for administrative staff to receive patients and store patient report data more easily. Make it easier for patient requirements and avoid confusion about requirements that are left behind or forgotten because this clinic information system is only designed to fill in data.